CORRUPTION CRIME: APPROACHES TO DEFINITION - A. A. Ivanova (Russian Journal of Economics and Law, 2012)
The article views anti-corruption legislation and gives ideas for its improvement. It is suggested to introduce the juridical notion of corruptive crime, and corruptive deal as its main indicator. The prospects of these innovative measures for anti-corruption policy realization are shown.